Տնտեսության տարածաշրջանային զարգացման մրցունակությունը - Հ. Վ. Խուրշուդյան (ՀՀ ԳԱԱ հրատ.)
Конкурентоспособность, стратегия устранения региональных диспропорций и поощрение сотрудничества между региональными органами власти и бизнес-сектором формируют предпосылки для региональной экономики. The competitiveness, strategies removing regional disproportions and encouraging cooperation between regional governments and business sector, form a premise for the regional economy.
Keywords: H Social Sciences; Economic Theory